DISCRETE-TIME MULTIVARIABLE CRITERION FOR LIMIT-CYCLE PREDICTIONS - Kouvaritakis, B; Cameron, R (1983)
Circulant matrices and their properties provide a new interpretation of limit-cycle phenomena in discrete-time nonlinear feedback systems. The present work extends the results of a recent paper in order to derive a multivariable circle type of criterion with a suitable Nyquist interpretation.